(untitled) (Educational Dimension, 2025)
This study explored how socio-demographic factors affect teachers’ resilience in selected secondary schools in Morogoro Municipality, Tanzania, using a mixed-method approach. Data were collected from 238 participants via questionnaires and interviews and analyzed with SPSS version 25. Key statistical methods, including binary logistic regression and chi-square tests, were employed to examine the relationships between socio-demographic variables and resilience that were measured by teachers’ resilience scale. The findings highlighted significant correlations between resilience levels and factors such as education, media exposure, and marital status. About half of the teachers showed high resilience, while the other half demonstrated low resilience, indicating diverse coping abilities. Teachers with higher educational qualifications and greater exposure to educational media exhibited better resilience and adaptive strategies. The study emphasizes the need for reforms in educational institutions and policies to enhance professional development and media access, ultimately aiming to improve teachers’ resilience in Tanzanian secondary schools.